Design and Modeling Simulation of a New Hydro-electric Hybrid Multi-function Continuously Variable Transmission - Wuyao Gou; Tao Deng; Ping Liu; Lu Zhang; Yang Yang (Jixie chuandong)
The traditional continuously variable transmission （CVT） is mainly divided into three transmission modes: hydraulic， mechanical and electric. The single transmission mode has obvious disadvantages， and the application field of composite CVT is still limited. Thus， a new hydro-electric hybrid multi-functional CVT is designed， which integrates the driving and braking energy regeneration functions of hydraulic and electric transmission， realizes the integration of mechanical energy， hydraulic energy and electric energy， and improves the performance and energy efficiency of the system. Through structural analysis and design， its working mode is formulated， and the joint simulation model of Solidworks， Matlab/Simulink and advisor is established for simulation verification under UDDS cycle. The simulation results show that the transmission structure can realize the designed continuously variable function， and the power performance， fuel economy and emission indexes of the whole vehicle are increased by 19.8%， 36.4% and 41.9% respectively at the cost of consuming about 10% SOC， which verifies the rationality and effectiveness of the CVT design.